The workplace as a learning environment - Moore, David Thornton (Journal of workplace learning, 2004)
Arguing against a concept of learning as only a formal process occurring in explicitly educational settings like schools, the paper proposes a conception of the workplace as a learning environment focusing on the interaction between the affordances and constraints of the social setting, on the one hand, and the agency and biography of the individual participant, on the other. Workplaces impose certain expectations and norms in the interest of their own continuity and survival, and in the interest of certain participants; but learners also choose to act in certain ways dependent on their own pr.